Cochlear implantation in Klippel Feil syndrome: pitfalls and outcomes - Chowdhary, Stuti; Asif, Syed Kamran; Varghese, Ajoy Mathew; John, Mary (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Cochlear implantation surgery involves multidisciplinary teamwork aiming for electrode insertion, which is as atraumatic as possible with an optimal intracochlear electrode position. Congenital inner ear anomalies often co-exist with musculoskeletal anomalies in syndromic children and can challenge cochlear implant surgery. The authors present a case of Klippel-Feil syndrome with congenital torticollis with bilateral inner ear anomalies who underwent cochlear implantation with multiple intra-operative surgical challenges. Multidisciplinary cooperation between the anesthetists, auditory-verbal therapy team, and the developmental pediatrics team is essential for a good outcome.